Illicit synthetic opioid consumption in Asia and the Pacific: Assessing the risks of a potential outbreak. (1st March 2021) - Taylor, Jirka; Pardo, Bryce; Hulme, Shann; Bouey, Jennifer; Greenfield, Victoria; Zhang, Sheldon; Kilmer, Beau
Highlights: Asia is home to the largest population of opioid users. Asia and the Pacific exhibit some signs of factors facilitating synthetic opioid emergence. Risk factors appear strongest in Australia, as does the country's ability to respond to a crisis. The region should work to improve early warning and data collection systems. Abstract: Background: Illegally manufactured potent synthetic opioids (IMPSO) like fentanyl have contributed to rises in overdose deaths in parts of North America and Europe. While many of these substances are produced in Asia, there is little evidence they have entered markets there. We consider the susceptibility to IMPSO's encroachment in markets in the Asia-Pacific region. Methods: Our analysis focuses on Australia, China, India, and Myanmar. Using a mixed-methods approach comprising interviews, literature review, and secondary data analyses, we examine factors facilitating or impeding incursion of IMPSO. Finally, we illustrate the potential for IMPSO fatalities in Australia. Results: Australia reports some signs of three facilitating factors to IMPSO's emergence: 1) existing illicit opioid markets, 2) disruption of opioid supply, and 3) user preferences. The other three countries report only existing illicit opioid markets. While diverted pharmaceutical opioids are a noted problem in Australia and India, heroin is the dominant opioid in all four countries. There are divergent trends in heroin use, with use declining in China, increasing in India, and stable in Australia and Myanmar. If IMPSO diffused in Australia as in North America from 2014 to 2018, and our assumptions generally hold, deaths from IMPSO could range from 1500–5700 over a five-year period. Conclusions: This analysis and illustrative calculations serve as an early indication for policymakers. With the exception of Australia, many countries in the region fail to properly record overdose deaths or monitor changes in local drug markets. Early assessment and monitoring can give officials a better understanding of these changing threats.